Relationship between Iron deposition and T lymphocytes in children with β-thalassemia with haematopoietic stem cell transplantation - Zhou, Yuhang; Luo, Jianming (Frontiers in Pediatrics, 2022)
Background: β-Thalassemia cellular immunity is associated with iron overload. However, the relationship between varying degrees of iron deposition and T cell immune recovery after allogeneic haematopoietic stem cell transplantation in children remain unclear. Methods: A retrospective analysis was performed on 73 children with β-Thalassemia undergoing sibling allogeneic haematopoietic stem cell transplantation. According to the hepatic T2* values, iron deposition was divided into three classes.T lymphocyte counts, serum ferritin, hepatic and cardiac T2* values were measured. Epstein–Barr virus and cytomegalovirus infection rates and graft-versus-host disease incidence were recorded. Results: Mild versus moderate group: The mild group had higher numbers of CD3, CD4, and CD8 cells than the moderate group at 1 month after allo-HSCT (P < 0.05). Mild versus severe group: The mild group had higher numbers of CD3 and CD8 cells than the severe group preoperatively and 1 month after allo-HSCT (P < 0.05). CD4 numbers in the mild group was greater than that in the severe group at preoperatively, 1, 3 and 6 months, and 1 year after allo-HSCT (P < 0.05). Moderate versus severe group: The moderate group had higher numbers of CD3, CD4, and CD8 cells than the severe group before allo-HSCT (P < 0.05). CD4 numbers were higher in the moderate group than in the severe group at 3 months after transplantation (P < 0.05). CD8 numbers were higher in the moderate group compared with the severe group at 6 months after transplantation (P < 0.05). Hepatic T2* values were positively correlated with CD3, CD4 and CD8 cells. The infection rates of epstein-barr virus and cytomegalovirus and the incidence of graft versus host disease were significantly different among the different iron deposition groups. Conclusion: Iron deposition affects immune recovery of T lymphocytes after allogeneic haematopoietic stem cell transplantation in children with thalassemia. The lower the levels of iron deposition, the greater the CD4 cell count.